UGA suppression by normal tRNA Trp in Escherichia coli: codon context effects. - Engelberg-Kulka, H (1981)
The nucleotide sequences at the 3' side of in-phase UGA termination codons in mRNAs of various prokaryotic genes were re-examined. An adenine (A) residue is found to be adjacent to the 3' side of UGA in mRNAs which code for readthrough proteins by the suppression of UGA by normal Escherichia coli tRNA Trp. It is suggested that the nature of the nucleotide following a UGA codon determines whether the UGA signals inefficiently or efficiently the termination of polypeptide chain synthesis: an A residue at this position permits the UGA readthrough process.